Analisis Pengaruh Sudut dan Kecepatan Putar Mata Pisau terhadap Kinerja Mesin Pencacah Pelepah Kelapa Sawit - Budi Setiawan; Suhendra; Naza (Jurnal Engine: Energi, Manufaktur, dan Material, 2026)
Oil palm was a leading oil-producing commodity used for both consumer and industrial purposes, while the waste in the form of oil palm fronds has potential as animal feed or compost. Utilizing this waste requires a shredding process to process it into these products. This study aims to determine the effect of blade angle and shaft rotational speed on the chipping results of oil palm fronds in an oil palm chipping machine. The parameters observed include machine chipping capacity, yield, and the percentage of good-sized chips. The study was conducted with three blade angle variations 15°, 25°, and 45° and three shaft rotation speeds 1,200–1,350 rpm, 1,400–1,550 rpm, and 1,600–1,750 rpm. Based on the test results, the chopper shaft rotational speed had a highly significant effect on chipping capacity, while the blade angle had a highly significant effect on both chipping capacity and the percentage of good-sized shreds. The highest chipping capacity was 45,55 kg/h, the highest chipping yield was 98.60%, and the highest percentage of good chip size was 97.88%.